Bojangles [videorecording (DVD)] - Hines, Gregory; Sargent, Joseph, 1925-2014; Haskins, James, 1941-2005 (Showtime Entertainment, 2002)
A look at the life of extraordinary tap dancing legend Bill "Bojangles" Robinson. This is the story of an incredibly talented man who struggled with the demons of his past and the racism of his time, but still entertained millions with his unique and complex dance style.